UV-A Supplement Improved Growth, Antioxidant Capacity, and Anthocyanin Accumulation in Purple Lettuce (Lactuca sativa L.) - Hengshan Qin; Yaliang Xu; Binbin Liu; Yong Gao; Yinjian Zheng; Qingming Li (Horticulturae, 2023)
This study investigated the impact of various light qualities on the growth, photosynthesis, antioxidant capacity, anthocyanin accumulation and associated gene expression in purple lettuce. The results showed that stem diameter, leaf number and dry mass of purple leaves lettuce increased significantly under white light plus red and blue light (WRB) plus 10 µmol·m−2·s−1 UV-A (SUV1), plus 20 µmol·m−2·s−1 UV-A (SUV2) and plus 30 µmol·m−2·s−1 UV-A (SUV3) treatments compared to white light plus red and blue light (WRB). Leaf expansion decreased with increasing UV-A doses, while fresh leaf mass was higher under SUV1 and SUV2 treatments. Photosynthesis parameters were improved under WRB, SUV1 and SUV2 treatments, with an increase in net photosynthetic rate (Pn), stomatal conductance (Gs) and transpiration rate (Tr) and a decrease in intercellular carbon dioxide concentration (Ci) under SUV3 treatment. Superoxide radical generation rate, hydrogen peroxide and malondialdehyde (MDA) content and relative conductivity increased significantly under SUV3 treatment. Anthocyanin content increased significantly with increasing doses of UV-A treatment, while related structural gene expression levels were upregulated more significantly by SUV2 and SUV3 treatments than WRB treatment. In summary, moderate UV-A supplementation can enhance the antioxidant system and promote anthocyanin accumulation in purple lettuce. Specifically, WRB plus 20 µmol·m−2·s−1 UV-A (SUV2) is recommended as an optimal light recipe for cultivating purple lettuce in protected horticulture.